MILENIAL DEPOSITOR BEHAVIOR IN ADOPTING DIGITAL BANKING - Handayani, Rini; Verdania Latif, Dini (International Journal of Psychosocial Rehabilitation, 2020)
The population of millenials in Indonesia has reached 63 million; this number is a fairly large number that is 24% of the productive population and constitutes the majority group. The Millennial generation is an active user of digital technology devices. This generation is faster and better understands services based on digital technology than the previous generation. As active users of digital technology devices, they are more focused on convenience and benefits and can be seen as a lucrative target market for digital banking. Millennial generation preferences will quickly change if it turns out that digital banking has poor performance. This study aims to determine the behavior of millennial generation in adopting digital banking This study seeks to explore and determine the behavior of millennial depositors in adopting digital banking using descriptive research designs. A questionnaire was used to determine the behavior of millennial depositors in adopting Digital Banking. The population in this study consisted of millennials residing in the city of Bandung, Indonesia, amounting to 912 thousand inhabitants. Samples to be taken are as many as 250 people. This study uses probability sampling, where all elements in the population are expected to have the same opportunity to be chosen. The results showed that in the behavior of depositors, behavioral control factors are very encouraging in the adoption of digital banking in millennial generation. The attitude factor has a fairly high impetus on the adoption of digital banking. Subjective norm factors provide a small impetus in the adoption of digital banking.